2015
DOI: 10.1111/epi.12910
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence between large‐scale ictal and interictal epileptic networks revealed by single photon emission computed tomography (SPECT) and electroencephalography (EEG)–functional magnetic resonance imaging (fMRI)

Abstract: SUMMARYObjective: Epilepsy is increasingly recognized as a network disorder, but the spatial relationship between ictal and interictal networks is still largely unexplored. In this work, we compared hemodynamic changes related to seizures and interictal spikes on a whole brain scale. Methods: Twenty-eight patients with refractory focal epilepsy (14 temporal and 14 extratemporal lobe) underwent both subtraction ictal single photon emission computed tomography (SPECT) coregistered to magnetic resonance imaging (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 42 publications
3
30
0
1
Order By: Relevance
“…A summary of equations of the model was provided in Table I. Taking into consideration previous reports about possible dysfunctions in the hyperemic response and oxygen metabolism in epileptogenic cortices [3][4][5][6][7][8][9], parameters ε and κ are of great interest in our study. ε is an unknown parameter in the model relating neuronal activity to the CBF.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A summary of equations of the model was provided in Table I. Taking into consideration previous reports about possible dysfunctions in the hyperemic response and oxygen metabolism in epileptogenic cortices [3][4][5][6][7][8][9], parameters ε and κ are of great interest in our study. ε is an unknown parameter in the model relating neuronal activity to the CBF.…”
Section: Methodsmentioning
confidence: 99%
“…The pathogenic relationships between the irritative zones and the seizure-onset zones are poorly understood in focal epilepsy [8]. Nevertheless, IEDs are accepted as specific EEG markers of interest for presurgical evaluation of epileptic patients, because they are very frequent paroxysmal and asymptomatic events, are easily recorded and provide high specificity for localizing seizureonset zones [9].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, some studies have shown that focal hypermetabolism and/or hyperperfusion may also occur during focal interictal spikes. 20,21 Electrographic seizures may emerge during PLEDs, coexist with PLEDs, or evolve on top of PLEDs 10,14 suggesting that seizures and PLEDs are distinct phenomena. PLEDs are resistant to treatment with antiepileptic drugs (AEDs).…”
Section: Introductionmentioning
confidence: 99%
“…Positron emission tomography (PET) and single-photon emission computerized tomography (SPECT) both have a long history of providing fundamental information regarding brain metabolism. Though lacking the time resolution of fMRI, they complement that methodology by having the ability to study such parameters as neurotransmitter-receptor interactions and local glucose metabolism for longer periods in time (minutes) (Price, 2012; Sander et al, 2013; Tousseyn et al, 2015). It is possible to perform fMRI and functional near-infrared spectroscopy (fNIRS) simultaneously, and such a multimodal approach may be used to improve the temporal resolution of the former, thus allowing better correlation of the BOLD signal with local hemodynamic changes (Steinbrink et al, 2006; Sato et al, 2013).…”
Section: Multimodal Studiesmentioning
confidence: 99%